Prebiotics in food and dietary supplements: a roadmap to EU health claims - Kieran Tuohy; Elaine E. Vaughan; Lucien F. Harthoorn; Ellen E. Blaak; Philip W. J. Burnet; Alessandro Busetti; Anirikh Chakrabarti; Nathalie Delzenne; Paul de Vos; Louise Dye; Damien Guillemet; Lesley A. Houghton; et al. (Gut Microbes, 2024)
Numerous studies have established that prebiotic ingredients in foods and dietary supplements may play a role in supporting human health. Over the three decades that have passed since prebiotics were first defined as a concept, research has revealed a complex universe of prebiotic-induced changes to the human microbiota. There are strong indications of a direct link between these prebiotic-induced changes and specific health benefits. However, at the present time, the EU has not permitted use of the term ‘prebiotic’ in connection with an approved health claim. This paper is the outcome of a workshop organized on the 25th October 2023 by the European branch of the International Life Science Institute (ILSI). It provides an overview of the regulatory requirements for authorized health claims in the EU, key areas of prebiotic research, and findings to date in relation to prebiotics and digestive, immune, metabolic and cognitive health. Research gaps and documentation challenges are then explored and a roadmap proposed for achieving authorization of ‘prebiotic’ in the wording of future EU health claims.